2014
DOI: 10.1186/1471-2415-14-161
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of fixed-combination bimatoprost/timolol versus fixed-combination dorzolamide/brimonidine/timolol in patients with primary open-angle glaucoma or ocular hypertension: a multicenter, prospective, crossover study

Abstract: BackgroundFixed-combination ocular hypotensives have multiple advantages, but triple-therapy dorzolamide/brimonidine/timolol (dorz/brim/tim) is only available in Latin and South America, and information on its relative efficacy is limited. This study compares the efficacy and tolerability of fixed-combination bimatoprost/timolol (bim/tim) and dorz/brim/tim in Mexican patients with primary open-angle glaucoma or ocular hypertension.MethodsIn this investigator-masked, crossover study, patients with unmet target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
0
13
0
2
Order By: Relevance
“…2012; Garcia‐Lopez et al. 2014). Some studies showed that triple therapy provides stronger IOP lowering effect, while some studies show that it is weaker than dual therapy.…”
Section: Limitationsmentioning
confidence: 99%
“…2012; Garcia‐Lopez et al. 2014). Some studies showed that triple therapy provides stronger IOP lowering effect, while some studies show that it is weaker than dual therapy.…”
Section: Limitationsmentioning
confidence: 99%
“…As mentioned above, topical therapies are often necessary to prevent the progression of glaucoma-related optic nerve damage, and here fixed combinations may be more beneficial than therapy with concomitant single agents. In accordance with this, KOF proved to be well tolerated and to have minimal harmful effects on the ocular surface [ 21 ].…”
Section: Discussionmentioning
confidence: 82%
“…In addition, the impact of tolerability on therapeutic adherence becomes a factor that contributes to the effectiveness of prolonged therapies. Previous clinical trials have demonstrated the efficacy of the triple-fixed combination KOF in treating POAG [ 17 , 21 , 22 ]. However, the preservative agent included in this formulation could potentially decrease tear film stability by altering the lipid component of the tear and perhaps produce dry eye syndrome by affecting the evaporative mechanism, producing irritation of the ocular surface [ 15 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Такая предопределенность может быть связана и с высокой вероятностью нарушений режима инстилляций со стороны пациента на всех этапах лечения. Многочисленные исследования доказали, что применение группы АПГ является наиболее эффек-тивным способом медикаментозной монотерапии глаукомы в плане 24-часового контроля уровня ВГД, а различия между препаратами внутри этой группы остаются незначительными [13][14][15][16][17][18][19][20].…”
Section: обзоры литературыunclassified
“…ст. соответственно [19]. Данные результаты были установлены при мониторировании уровня офтальмотонуса в течение 90 сут наблюдения и отличались статистической достоверностью (р < 0,001).…”
Section: обзоры литературыunclassified